Cost And Scale Efficiency Of Rice Farmers In Soc Trang Province, Vietnam - La Nguyen Thuy Dung; Quoc Nghi Nguyen (Cita konsultindo, 2025)
Through the application of a non-parametric method, the research focused on measuring cost efficiency based on estimating technical efficiency and allocative efficiency in resources of rice farmers in Soc Trang Province, Vietnam. Moreover, the research centered on its values through the estimated and compared scale efficiency in the production of farmers. Research data was collected from 240 rice farmers who have been cultivating rice in My Tu and Thanh Tri districts, Soc Trang Province. The Data Envelopment Analysis (DEA) was used to estimate the effective component of rice farmers. The results showed that rice farmers achieved relatively high scale efficiency whereas the cost efficiency only was an average proportion.